Facility Management in Supporting Scientific Writing Learning at SMAN 10 Surabaya - Nuphanudin; Nayla Dea Adelia; Raya Naila Feisya; Zulfa Sekar Arum (The Indonesian Institute of Science and Technology Research, 2026)
This study explores how facility and infrastructure management support scientific writing learning at SMAN 10 Surabaya. Scientific writing is a critical academic competence that requires not only cognitive and literacy skills but also an enabling learning environment supported by adequate educational resources. Using a descriptive qualitative approach, this research investigated the availability of facilities, the roles of teachers and students in facility utilization, and collaborative management strategies that contribute to learning quality improvement. Data were collected through semi-structured interviews with teachers, guidance counselors, school administrators, and students, complemented by direct observations of facility use and document analysis of school inventory and development plans. The findings reveal that SMAN 10 Surabaya provides baseline infrastructure, including a school library, computer laboratories, internet access, and digital learning resources, which collectively support students’ academic writing practices. However, limitations remain in terms of updated references, computer availability, and digital access consistency. Teachers play a pivotal role as facilitators by integrating digital academic tools such as Google Scholar, Mendeley, and online mentoring platforms to scaffold students’ writing development. Students actively engage in constructivist learning practices through exploration, collaboration, and iterative writing revisions. Furthermore, facility governance is strengthened through participatory planning, transparent procurement, routine maintenance, and continuous evaluation involving multiple stakeholders. Overall, the study concludes that strategic, collaborative, and adaptive facility management functions as a key enabler of scientific writing learning and educational quality enhancement.